2021
DOI: 10.1093/asj/sjab152
|View full text |Cite
|
Sign up to set email alerts
|

The Difference in Facial Movement Between the Medial and the Lateral Midface: A 3-Dimensional Skin Surface Vector Analysis

Abstract: Background Our understanding of the functional anatomy of the face is constantly improving. To date, it is unclear whether the anatomic location of the line of ligaments has any functional importance during normal facial movements such as smiling. Objectives It is the objective of the present study to identify differences in facial movements between the medial and lateral midface by means of skin vector displacement analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This is in alignment with currently accepted treatment algorithms that predominantly target deep = supraperiosteal fascial layers to reshape and revolumize various facial regions including the midface. These observations are also in line with the previously established treatment principles for minimally invasive facial aesthetic procedures which were confirmed in independent clinical studies: lateral face first, upper face first, and deep layers first 1,5–7 …”
Section: Introductionsupporting
confidence: 88%
“…This is in alignment with currently accepted treatment algorithms that predominantly target deep = supraperiosteal fascial layers to reshape and revolumize various facial regions including the midface. These observations are also in line with the previously established treatment principles for minimally invasive facial aesthetic procedures which were confirmed in independent clinical studies: lateral face first, upper face first, and deep layers first 1,5–7 …”
Section: Introductionsupporting
confidence: 88%
“…Objective outcome assessment relied on 3‐dimensional (3D) imaging as previously described 3,16,17 . In brief, standardized full‐face 3D images were obtained utilizing a Vectra H2 camera system (Canfield).…”
Section: Methodsmentioning
confidence: 99%
“…One of the major effects of facial aging is a descent of facial soft tissue. This is facilitated by the mobility of the fascial layers—greater in the medial midface compared to the lateral midface 26 . In the medial midface, the increased mobility is needed because of the interaction between facial muscles and the overlying skin; without such mobility, muscle contraction would not result in the skin surface movements that we interpret as facial expressions.…”
Section: Discussionmentioning
confidence: 95%
“…This is facilitated by the mobility of the fascial layers-greater in the medial midface compared to the lateral midface. 26 In the medial midface, the increased mobility is needed because of the interaction between facial muscles and the overlying skin; without such mobil- Age-related soft tissue descent changes the relative location of some of the superficial fat compartments, but does not affect the deep midfacial fat compartments. 31,32 Recent anatomic experimental studies have demonstrated the stability of the deep midfacial fat compartments, and this observation is exploited clinically by the use of the supra-periosteal plane of the midface as the major area for augmentation to recreate a foundation for the overlying midfacial fascial layers.…”
Section: Discussionmentioning
confidence: 99%